Effect of Jatropha(Jatropha curcas L.) Seeds Extract Induction on Liver Histopathology and SGPT levels (Serum Glutamic Piruvic Transaminase) on Rat (Rattus norvegicus) - Fitria, Neny; Pratiwi, Herlina; Widodo, Edwin; Primajayanti, Angelia; Anggraini, Novia Dwi; Nurfitriani, Nurfitriani; Findi, Nadia (Veterinary Biomedical and Clinical Journal, 2021)
Jatropha or Jatropha curcas L. is a plant of the Euphorbiaceae family with medicinal and non-medical uses, including oral contraceptives. The part of Jatropha that is often used is the seed. However, Jatropha seed also contains saponins, phorbol esters, currants, tannins which can cause organ poisoning. This study was conducted to determine the effect of Jatropha seed extract on liver histopathology and SGPT levels in Rattus Norvegicus rats, using a completely randomized design method. Experimental animals were divided into four groups, and each group consisted of five female rats. The groups were the control group without treatment and those treated with Jatropha seed extract orally at doses of 10, 50, and 100 mg/kg BW. The induction process was carried out every day for 14 days, on the 15th day, a necropsy was performed. Livers were taken for histological analysis, and blood samples were taken to measure SGPT levels. Results showed that the administration of Jatropha seed extract could increase SGPT levels. The administration of Jatropha seed extract at a dose of 100 mg/kg body weight induced the most severe damage of hepatocytes among the treatment groups.